Exploring the Autoimmune Spectrum: A Case Study - Haque, Fahim; Dey, Gourab; Paul, Nandita; Ahmed, Akhlak (Bangladesh Journal of Medicine, 2024)
Idiopathic thrombocytopenic purpura (ITP) is a condition characterized by a low platelet count, leading to an increased risk of bleeding. Despite having a shared autoimmune aetiology, documented cases of ITP alongside other autoimmune diseases are scarce. Here, we describe the case of a 55-year-old Bangladeshi woman who presented with bleeding symptoms and generalized weakness. On query, she gave a history of dry eye and dry mouth. She was a known case of hypothyroidism and ischaemic heart disease. After comprehensive evaluation, she was diagnosed with acute idiopathic thrombocytopenic purpura, along with Sjogren’s syndrome, Hashimoto’s thyroiditis, an old antero-septal myocardial infarction, dyslipidemia, and grade I fatty liver disease. Treatment involved a combination of immunosuppressive therapy, thrombopoietin receptor agonists (TPO-RA) - eltrombopag, platelet transfusion, levothyroxine, and supportive measures leading to successful management. This case highlights the challenge of addressing multiple autoimmune conditions concurrently and stresses the importance of comprehensive evaluation and multidisciplinary care to diagnose and manage these complex presentations accurately. Notably, patients with ITP may harbour other undiagnosed autoimmune conditions and face an elevated risk of malignancy in the future. Despite this, in Bangladesh, the prevalence of autoimmune diseases, including ITP, remains poorly understood. Further research is crucial to elucidate the epidemiology and clinical characteristics of autoimmune diseases associated with ITP in this population, enhancing our ability to provide effective care and public health interventions. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 180